Johannes Ockeghem: Missa Ecce ancilla domini - Ockeghem, Johannes c. 1410-1497; Benthem, Jaap van (Utrecht Koninklijke vereniging voor Nederlandse muziekgeschiedenis, 1995)
The Missa Ecce ancilla Domini by Johannes Ockeghem is based on the concluding segment of a fairly rare plainsong, the long processional antiphon Missus est angelus Gabriel, sung on Sundays during Advent in the rite of Paris. The text of the antiphon is drawn from the Gospel of Luke (Luke 1: 2638), and relates the story of the Annunciation; the segment that Ockeghem selected as a cantus firmus is Marys reply to the angel Gabriel that precipitated the Incarnation: Behold the handmaid of the Lord, do unto me according to Thy Word. That Ockeghem composed this Mass to celebrate the Annunciation is confirmed by the illumination adorning the opening in one of its two sources, the Chigi Codex (Vatican City, Biblioteca Apostolica Vaticana, MS Chigi C VIII 234), a lavish manuscript prepared for Philippe Bouton, Seigneur of Corberon, probably soon after Ockeghems death in 1497. Bouton is likely to have had personal contact with Ockeghem on four separate occasions in the 1460s and 1470s, and the Chigi Codex, with its extraordinary concentration of music by Ockeghem, seems intended in part as a memorial to the composer. (Although it has been generally assumed that the scribe of the Chigi Codex was employed by a scriptorium intimately associated with the Burgundian-Hapsburg court, an institution with which Bouton had official ties, the flawed readings of music by the court singer and composer Alexander Agricola contained in this and other codices copied by this scribe have called this assumption into question).